Using Dissemination Research Approaches to Understand the Awareness, Adoption, and Use of The Program Evaluation Standards - Julie Morrison; Kathleen Cunningham (Journal of MultiDisciplinary Evaluation, 2023)
Background: The adoption and use of effective, legally defensible, and ethically sound practices relies on the successful dissemination of evidence-based practices and professional standards. The field of program evaluation has standards, competencies, and principles, yet little is known about how these are utilized by education-focused program evaluators.